Has integrated medical insurance scheme enhanced happiness of returning migrant workers? Evidence from China - Shen, Yupeng; Meng, Yiming; Shan, Yiyue; Zhang, Shichen; Tang, Daorui; Sun, Zhengxiu (Frontiers in Public Health, 2024)
Using four waves of panel data from the China Labor-force Dynamic Survey (CLDS) spanning from 2012 to 2018, regarding gradual reforms of the Integrated Medical Insurance Scheme (IMIS) in China as a quasi-experiment, we establish a time-varying difference-in-differences (DID) model to systematically examine the impact of IMIS on the happiness of returning migrant workers. Further, a structural equation model is employed to explore the potential mechanisms and analyze the heterogeneity of the effect. The results indicate that IMIS significantly enhances the happiness of returning migrant workers, which remains robust after a series of robustness checks. In addition, this effect operates through two potential mechanisms, economic effects and integration effects, which account for 25.59 and 29.31% of the total effect, respectively. Compared to the older generation, low-income, low-health human capital, and high-reimbursement level regions, the enhancement of happiness due to IMIS is more pronounced among the new generation, high-income, high-health human capital, and low-reimbursement level regions of returning migrant worker, which might exhibit a “pro-wealth” characteristic. The findings provide empirical support and policy implications for continuously improving the health insurance system, promoting the equalization of basic public services between urban and rural areas, and consistently enhancing the happiness of returning migrant workers.